Australian Foreign Politics on Indonesia: A Case Study of West Irian 1949-1962 - Budi Purnomo (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This paper examines Australian foreign policy among Indonesian, especially on the West Irian case in 1949-1962. The bilateral relationship between Indonesia-Australia from 1949-1962 always goes through up and down “Roller Coaster.” The relationship between both countries is not structured. No mechanism is arranged, so it depends on the political development and the situations, especially defense and political problems. Indonesia claimed that West Irian is supposed to be a menace for Australian security. Australia put West Irian as a Vital Interest concept. In the cabinet session on January 11, 1962, Australia do “Volte Face” and confess that the vital interest concept is not invalid anymore because there is no menace evidence for Australia or region Australia interest.